2017
DOI: 10.1371/journal.pone.0175881
|View full text |Cite
|
Sign up to set email alerts
|

The importance of calcium in improving resistance of Daphnia to Microcystis

Abstract: Changing environmental calcium (Ca) and rising cyanobacterial blooms in lake habitats could strongly reduce Daphnia growth and survival. Here, we assessed the effects of maternal Ca in Daphnia on transfer of resistance to their offspring against Microcystis aeruginosa PCC7806 (M. aeruginosa). Laboratory microcosm experiments were performed to examine effects in Daphnia carinata (D. carinata) and Daphnia pulex (D. pulex), and that how Ca induce responses in their offspring. The results showed that growth and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Ingestion of calcium carbonate in CCA may aid in trituration of food by the pharyngeal jaws (Carr et al 2006), releasing cells from the thick mucilaginous sheaths of these filamentous cyanobacteria. If some cyanobacteria are toxic, such as Lyngbya majuscula (Albert et al 2005;Engene et al 2012Engene et al , 2013Taylor et al 2014), ingestion of CCA might serve to reduce toxicity as calcium has been shown to protect Daphnia from toxin of the cyanobacterium Microcystis (Akbar et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of calcium carbonate in CCA may aid in trituration of food by the pharyngeal jaws (Carr et al 2006), releasing cells from the thick mucilaginous sheaths of these filamentous cyanobacteria. If some cyanobacteria are toxic, such as Lyngbya majuscula (Albert et al 2005;Engene et al 2012Engene et al , 2013Taylor et al 2014), ingestion of CCA might serve to reduce toxicity as calcium has been shown to protect Daphnia from toxin of the cyanobacterium Microcystis (Akbar et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The D. pulex-pulicaria complex is one of the most vulnerable Daphnia species to Ca limitation because of its high Ca needs [ 8 , 13 ]. Studies have also reported combined effects on daphniid survival and reproduction of Ca stress and its potential interactions with UV radiation [ 14 ], metal and pharmaceutical toxicity [ 15 , 16 , 17 ], poor food quality [ 8 , 18 , 19 , 20 ], and the presence of invertebrate predators [ 21 ]. The swimming behaviour of Daphnia may also be influenced by low Ca availability at higher temperatures [ 22 ].…”
Section: Introductionmentioning
confidence: 99%